RECONSTRUCTING ARABIC LANGUAGE LEARNING STRATEGIES THROUGH A HOME-BASED LANGUAGE ACQUISITION (HBLA) APPROACH - Muslim, Buhori; Bukhari, Najwa (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
In teaching Arabic as a Foreign Language (AFL), a common problem often appears: students aren't able to speak well even after years of learning. This happens when students can’t communicate well even after a long time in formal classes. The problem comes up partly from very organized ways of teaching that don't focus enough on using language in real situations. However, learning a first language at home, called Home-Based Language Acquisition (HBLA), works very well because it's natural and immersive. This research finds a missing piece: there isn't a full model that recreates the HBLA system for use in AFL classrooms. The goal of this research is to change how Arabic is taught by using key ideas from HBLA. Specifically, the research aims to create a complete teaching model that can fix the difference between what students know about grammar and what they can do in communication. A qualitative design research method was used, with a Systematic Literature Review (SLR) guided by the PRISMA framework. Information from journal articles, books, and academic papers was gathered, checked, and studied for themes to find the main ideas of HBLA. These ideas were then put together to create a clear conceptual model. The findings show that the SLR identified four basic HBLA principles: (1) lots of understandable input, (2) social interaction with help, (3) a good emotional environment, and (4) learning that is based on real situations and focused on function. Based on these principles, the study suggests a combined HBLA teaching model (HBLA-IPM), which has four connected parts: deep input, mediated interaction, emotional support, and functional outcomes. Together, these parts create a full learning environment that changes the focus from just teaching grammar to using language in a meaningful way. It concludes that the HBLA-IPM offers a new theoretical and practical way to change Arabic language teaching. The model especially encourages teachers to change from just giving knowledge to helping and guiding, and it asks curriculum designers to use competency-based syllabi and real assessments. Although it's conceptual and needs more real-world testing, this model gives a strong framework for creating more human, effective, and empowering learning experiences, with the final goal of making confident and skilled Arabic language speakers.